Google Loon Sebagai Solusi Terkini Koneksivitas Internet Di Daerah Pedalaman Dan Terpencil - Zulfan Zulfan; Muhammad Chaidir; Lulu Huril In (Faculty of Science and Technology Universitas Islam Negeri Ar-Raniry, 2016)
Result of this study shows that two of three of its users around the world, internet is not reachable technology especially in hinterland and remote area.Usage of satellite and optic fiber for internet system in those areas is not affordable. By using Google Loon technology,internet users in the areas can access internet.Google Loon is able to spread accessibility of internet up to 1250 kmÂ²(wide) or 40 km diameter), and speed of accessibility reaches 3G(10Mbps)